2009
DOI: 10.1038/nature08595
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sequential polyubiquitylation on a millisecond timescale

Abstract: The pathway by which ubiquitin chains are generated on substrate via a cascade of enzymes consisting of an E1, E2 and E3 remains unclear. Multiple distinct models involving chain assembly on E2 or substrate have been proposed. However, the speed and complexity of the reaction have precluded direct experimental tests to distinguish between potential pathways. Here we introduce new theoretical and experimental methodologies to address both limitations. A quantitative framework based on product distribution predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(248 citation statements)
references
References 21 publications
11
234
1
2
Order By: Relevance
“…Although the activation of the intrinsic activity of a CRL is one mode of regulation by neddylation, it is not the only one. Indeed, CRL neddylation can block association with the CAND1 exchange factor and enhance association with the CSN complex, as described in detail below.In the on state, CRLs can be highly processive, giving rise to multiple catalytic cycles before substrate dissociation [70][71][72]. This feature has much to do with how a CRL-specific, ubiquitinchain-forming E2 associates with the cullin-RING E3 scaffold.…”
mentioning
confidence: 99%
“…Although the activation of the intrinsic activity of a CRL is one mode of regulation by neddylation, it is not the only one. Indeed, CRL neddylation can block association with the CAND1 exchange factor and enhance association with the CSN complex, as described in detail below.In the on state, CRLs can be highly processive, giving rise to multiple catalytic cycles before substrate dissociation [70][71][72]. This feature has much to do with how a CRL-specific, ubiquitinchain-forming E2 associates with the cullin-RING E3 scaffold.…”
mentioning
confidence: 99%
“…We next compared the kinetics of San1 peptide ubiquitylation with the kinetics of a reaction catalyzed by the SCF ubiquitin ligase as the rates of ubiquitin transfer to SCF-bound substrates are among the fastest in the literature (54). Singleturnover ubiquitylation reactions were assembled with either yeast Cdc34 or Ubc1 and San1 or with SCF in combination with both UbcH5c and human Cdc34 (note that SCF has been shown to function synergistically with these E2s; Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast WT and ⌬190 Cdc34 were expressed and purified as previously described (51,54). Yeast Ubc1 was expressed and purified essentially as previously described (46) with the following modifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quench-flow experiments have revealed that SCF/Cdc34 catalyzes ubiquitination in a progressive manner, with the addition of one Ub at a time (30). SCF appears to engage Cdc34 during the elongation reaction via a two-step mechanism.…”
Section: Discussionmentioning
confidence: 99%